AN ANALYSIS ON GRAMMATICAL ERRORS IN WRITING DESCRIPTIVE TEXT AT MTS NEGERI LABUHANBATU SELATAN - Siregar, Sholahuddin (BRIGHT VISION Journal of Language and Education, 2024)
Based on the findings and discussions in the previous chapter, the researcher concluded the type of errors are usually made by the second grade students of MTsN 2 Labuhanbatu using writing descriptive text, and the cause of errors made by the second grade students of MTsN 2 Labuhanbatu using writing descriptive text. The conclutions are as follows The type of errors are usually made by the second grade students of MTsN 2 Labuhanbatu using descriptive text. Based on the description in previos chapter, it can be concluded that the second grade of MTsN 2 still made the errors when the students were asked to a descriptive text. The types of errors made by the students on writing descriptive text are based on surface strategy taxonomy which are classified into omission, addition, misformation, and misordering. After counting the errors, the researcher found 35 total of errors consisting of 16 errors of omission, 8 errors of addition, The cause of errors made by the second grade students of MTsN 2 Labuhanbatu using writing descriptive text. After analyzing each types of errors found in descriptive text in students writing of the second grade of MTsN 2 Labuhanbatu, the researcher can find some causes of errors. They are interlingual and intralingual transfer. Interlingual transfer is errors that are influenced by the interference of users mother tongue. The users still apply Indonesian pattern into English when they translate the sentences. Then intralingual transfer occurs when students get difficulty learn the second language.